USE OF ACRYLIC RESIN PROSTHESES IN THE TREATMENT OF RHINOTHECAL FRACTURES - Marchio, Maria Ângela Panelli [UNESP]; Magalhães, Thaís Vendramini [UNESP]; Minto, Bruno Watanabe [UNESP]; Dias, Luís Gustavo Gosuen Gonçalves [UNESP] (American Association of Zoo Veterinarians, 2022)
This report describes the use of synthetic acrylic resin prostheses in five birds with rhinothecal fracture. Satisfactory biomechanical and clinical results were obtained in all cases, enabling early return to function of the beak. The patients, a roadside hawk (Rupornis magnirostris; case 1), a cockatiel (Nymphicus hollandicus; case 2), two turquoise-fronted parrots (Amazona aestiva; cases 3 and 4), and a maritaca (Pionus maximiliani; case 5), all suffered rhinothecal fractures with extensive bone loss, resulting in malnutrition, dehydration, and difficulty in handling food. An acrylic prosthesis was chosen in all cases, with the resin mold formed with two 1.0-mm pins in four cases, and cerclage wires in case 2. All birds made an excellent recovery and showed early use of the beak, with no complications for up to 15 mon. After 21 d of observation, the patients were moved to zoo enclosures for rehabilitation. The treatment of rhinothecal fractures is very challenging and requires a combination of orthopedic and dental techniques to provide full recovery of the species' natural functions.